A Discourse Analysis of Lexical Cohesion In The Novel ‘Jane Eyre’ By Charlotte Bronte - Andi Hudriati; Muhammad Basri Dalle; Chichi Indriany (Fakultas Sastra - Universitas Muslim Indonesia, 2016)
The aims of this research were to describe the reiteration and to know the collocation in the novel ‗Jane Eyre‘ by Charlotte Bronte and it was analyzed by using the descriptive method. It was to indicate the lexical cohesion. This research described the methods which commonly consisted of two techniques, namely data collection and data analysis. Data collection consisted of the text of the novel Jane Eyre‘ by Charlotte Bronte and data analysis consisted of the tables of cohesive items through the novel, 80 sentences taken from the first chapter. The results of this study found out that there were two types of lexical cohesion, namely reiteration and collocation. It could be seen in the novel Jane Eyre‘ by Charlotte Bronte that there were 4 kinds of reiteration which had found, they were 5 items of repetition, 17 items of synonym, 4 items of superordinate, and 6 items of general word. Besides, there were 6 items of collocation. So that, the writer concluded that the author (Charlotte Bronte) mostly used synonym to avoid repetition in her novel especially in the first chapter under the title Gateshead. Meanwhile, this result hopefully would motivate the people to learn about discourse analysis moreover to know about lexical cohesion itself.